RNA modifications in cardiovascular health and disease - Gatsiou, Aikaterini; Stellos, Konstantinos (Nature reviews. Cardiology, 2023)
RNA is not always a faithful copy of DNA. Advances in tools enabling the interrogation of the exact RNA sequence have permitted revision of how genetic information is transferred. We now know that RNA is a dynamic molecule, amenable to chemical modifications of its four canonical nucleotides by dedicated RNA-binding enzymes. The ever-expanding catalogue of identified RNA modifications in mammals has led to a burst of studies in the past 5 years that have explored the biological relevance of the RNA modifications, also known as epitranscriptome. These studies concluded that chemical modification of RNA nucleotides alters several properties of RNA molecules including sequence, secondary structure, RNA-protein interaction, localization and processing. Importantly, a plethora of cellular functions during development, homeostasis and disease are controlled by RNA modification enzymes. Understanding the regulatory interface between a single-nucleotide modification and cellular function will pave the way towards the development of novel diagnostic, prognostic and therapeutic tools for the management of diseases, including cardiovascular disease. In this Review, we use two well-studied and abundant RNA modifications — adenosine-to-inosine RNA editing and N6-methyladenosine RNA methylation — as examples on which to base the discussion about the current knowledge on installation or removal of RNA modifications, their effect on biological processes related to cardiovascular health and disease, and the potential for development and application of epitranscriptome-based prognostic, diagnostic and therapeutic tools for cardiovascular disease.